Influence of zwitterionic buffer effects with thermal modification treatments of wood on symbiotic protists in Reticulitermes grassei Clément - Duarte, Sónia (2021)
The majority of thermal modification processes are at temperatures greater than 180 C, resulting in a product with some properties enhanced and some diminished (e.g., mechanical properties). However, the durability of thermally modified wood to termite attack is recognised as low. Recent attempts at combining thermal modification with chemical modification, either prior to or directly after the thermal process, are promising. Buffers, although not influencing the reaction systems, may interact on exposure to certain conditions, potentially acting as promoters of biological changes. In this study, two zwitterionic buffers, bicine and tricine, chosen for their potential to form Maillard-type products with fragmented hemicelluloses/volatiles, were assessed with and without thermal modification for two wood species (spruce and beech), with subsequent evaluation of their effect against subterranean termites (Reticulitermes grassei Clément) and their symbiotic protists. The effect of the wood treatments on termites and their symbionts was visible after four weeks, especially for spruce treated with tricine and bicine and heat treatment (bicine HT), and for beech treated with bicine and bicine and heat treatment (bicine HT). The chemical behaviour of these substances should be further investigated when in contact with wood and also after heat treatment. This is the first study evaluating the effect of potential Maillard reactions with zwitterionic buffers on subterranean termite symbiotic fauna